Primary School Teacher’s Views on the Purpose and Forms of Student Performance Assessment - Niaoustas, Georgios (Universitas Pendidikan Ganesha, 2024)
Assessment is a complex and dynamic process and an integral part of teaching and learning. It is an issue that concerns the state, educators and scientists, teachers, parents, and students. This study aims to analyze the views of primary school teachers. A questionnaire was used as the research method. The findings of the research revealed that most teachers agree with the assessment of student performance, considering it mostly a quality process that must move according to the described logic. They generally apply a Formative Assessment while applying a Diagnostic Assessment and Summa-tive Assessment depending on the time of the teaching process. The teachers also state that the assessment is primarily aimed at measuring the achieve-ment of the teaching objectives, feedback, identification of the learning dif-ficulties, and determination of the special inclinations/abilities of the students. The majority of the teachers of Aetoloakarnania who participated in the research, expressed a positive attitude toward the assessment of the student's performance. Teachers believe that the assessment of student performance from a pedagogical view-point is a qualitative process, during which all the parameters that influence it should be considered. They also argue that it should be aimed at controlling the student’s progress in relation to his or her previous performance, while at the same time recommending a process to measure the achievement of the teaching objectives.